Microbiological And Organoleptic Quality Of Yellow Fin tuna (Thunnus albacores) Fillet During Cold Storage - Christian Derwin Sorongan; Joyce Valencia Palenewen; Hens Onibala; Henny Adeleida Dien; Engel Pandey; Feny Mentang (Sam Ratulangi University, 2022)
Fish fillet is a piece of fish meat obtained by slicing whole fish, along the spine starting from the head to near the tail. Generally, fish fillet processors store fish fillet products in cold storage to extend shelf life. Vacuum packaging of the product will prevent contamination and increase the shelf life of the product. This study aims to analyze the quality of yellowfin tuna fillets and changes during cold storage. And with the given treatment, the fish fillet products were packaged in vacuum and without vacuum with a storage period of 0 days, 3 days 6 days and 9 days. The parameters tested in this study were the organoleptic test, pH test, and Total Plate Number (ALT). The results showed that vacuum-packed tuna fillets were of better quality than those packaged without vacuum. With organoleptic results, the appearance value was 8, the smell was 7.8, and the texture was 8.2 and the ALT value was 2.9 x 104 cfu/gram.Keywords: fish fillet, organoleptic, ph , ALT. ABSTRAKFillet ikan adalah bagian daging ikan yang diperoleh dengan penyayatan ikan utuh, sepanjang tulang belakang dimulai dari kepala hingga mendekati ekor. Umumnya pengolah fillet ikan meyimpan produk fillet ikan pada penyimpanan suhu dingin untuk memperpanjang masa simpan. Pengemasan vakum pada produk akan mencegah kontaminasi dan menambah lama masa simpan produk. Penelitian ini bertujuan untuk menganalisa mutu fillet ikan tuna sirip kuning dan perubahan selama penyimpanan suhu dingin. Dan dengan perlakuan yang diberikan yaitu, produk fillet ikan dikemas vakum dan tanpa vakum dengan lama penyimpanan 0 hari, 3 hari 6 hari dan 9hari. Parameter yang diuji dalam penelitian ini adalah uji organoleptic uji ph, dan Angka Lempeng Total (ALT). Hasil penelitian menunjukkan bahwa fillet ikan tuna yang dikemas vakum mendapatkan mutu lebih baik dari pada yang dikemas tanpa vakum. Dengan hasil organoleptic nilai kenampakan 8, bau 7,8, dan tekstur 8.2 dan nilai ALT 2.9 x 104 cfu/gram. Kata Kunci : fillet ikan, organoleptik, ph , ALT.